Virtual Identity of PSS Sleman Fans on Twitter Account @CampusBoys1976 - Lastrafila V Alnoriz; Tri Hastuti Nur Rochimah (Jogjakarta Communication Conference (JCC), 2023)
The transformation of communication technology has improved fan cultural practices and produced new media that can encourage the formation of virtual fandom. New media such as Twitter became a practical alternative to the virtual fandom of football clubs in forming the desired identity. This study aims to find out how fans of the PSS Sleman football club built a virtual identity on the Twitter account @CampusBoys1976. The research method used is the netnography method with the technique of collecting participant observation data and literature studies. The results showed that Twitter accounts @CampusBoys1976 use three ways to build a virtual identity as PSS Sleman fans who provide support through literacy culture, which were displayed on Twitter pages, activity on Twitter, and the use of text language associated with Twitter affordances and events that occur.